Critical review on biogeochemical dynamics of mercury (Hg) and its abatement strategies. (April 2023) - Singh, Arun Dev; Khanna, Kanika; Kour, Jaspreet; Dhiman, Shalini; Bhardwaj, Tamanna; Devi, Kamini; Sharma, Neerja; Kumar, Pardeep; Kapoor, Nitika; Sharma, Priyanka; Arora, Priya; Sharma, Anket; et al.
Abstract: Mercury (Hg) is among the naturally occurring heavy metal with elemental, organic, and inorganic distributions in the environment. Being considered a global pollutant, high pools of Hg-emissions ranging from >6000 to 8000 Mg Hg/year get accumulated by the natural and anthropogenic activities in the atmosphere. These toxicants have high persistence, toxicity, and widespread contamination in the soil, water, and air resources. Hg accumulation inside the plant parts amplifies the traces of toxic elements in the linking food chains, leads to Hg exposure to humans, and acts as a potential genotoxic, neurotoxic and carcinogenic entity. However, excessive Hg levels are equally toxic to the plant system and severely disrupt the physiological and metabolic processes in plants. Thus, a plausible link between Hg-concentration and its biogeochemical behavior is highly imperative to analyze the plant-soil interactions. Therefore, it is requisite to bring these toxic contaminants in between the acceptable limits to safeguard the environment. Plants efficiently incorporate or absorb the bioavailable Hg from the soil thus a constructive understanding of Hg uptake, translocation/sequestration involving specific heavy metal transporters, and detoxification mechanisms are drawn. Whereas recent investigations in biological remediation of Hg provide insights into the potential associations between the plants and microbes. Furthermore, intense research on Hg-induced antioxidants, protein networks, metabolic mechanisms, and signaling pathways is required to understand these bioremediations techniques. This review sheds light on the mercury (Hg) sources, pollution, biogeochemical cycles, its uptake, translocation, and detoxification methods with respect to its molecular approaches in plants. Graphical abstract: Image 1 Highlights: Anthropogenic activities are expediting the generation and accumulation of mercury in soil, water, and other biological systems. Mercury toxicity relies on its bioavailability, whereas its uptake in plants leads to its biomagnification into the biological food chains. These toxicants hamper the plants metabolism as well as act neurotoxic and immunotoxic to human health. Phytoremediation and microbial remediation strategies are sustainable methods and have an edge over conventional methods to treat Hg pollutants. In plants the Hg detoxification mechanism involves the activation of certain enzymatic and non-enzymatic antioxidants and bacterial-associated Mer proteins.